(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The toxic and adaptive mutagenic effects of five aminoglycoside antibiotics (ampliclox, tetracycline, septrin, amoxicillin and ciprofloxacin) on germination and growth of white and yellow maize varieties were investigated. Seeds were subjecting to different concentrations of the antibiotics (0%, 0.0005%, 0.005%, 0.05%, 0.5% and 1%) and rinsed in distilled water before planting directly into the soil. The experimental design adopted was Completely Randomized Design with four replicates each. The phytotoxic impact of these antibiotics varied with the maize varieties and different concentrations used. All the maize seeds subjected to 1% of all the antibiotics had lower rates of germinations except for 1% ampliclox and control. It was found that both white and yellow maize varieties treated with the lower concentrations (0.0005 and 0.05%) of the antibiotics especially ampliclox exhibited highest amount of number of leaves, dry weight, number of days to flowering and number of grains while higher concentrations (0.5 and 1%) had limiting effects on the maize plants. The present study thus show that ampiclox drug had the highest percentage rate, highest number of leaves, dry weight, number of days to flowering and number of grains at lower concentration compared to the other drugs at the same concentration among the yellow and white maize varieties